Development of a Graphic Design Learning Module for the Deaf and Hard-of-Hearing (DHH) Students Based on Technology and Learning Style in Malaysian TVET institutions. - et. al., Zainuddin Ibrahim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Graphic Design is used in many industries and involves both the knowledge and skills in creating artefacts. Many Deaf and hard-of-hearing (DHH) students, especially in the Technical and Vocational Education and Training (TVET) institutions are attracted in pursuing studies in this field, perhaps due to the visual nature of the course. However, learning graphic design is challenging for DHH students due to the technologies and teaching approach applied in these institutions. A module which was designed with experts, was implemented in a selected polytechnic which offered the graphic design course for the deaf and non-deaf students. The module used videos and other resources for the different learning styles, as well as a discussion platform on Padlet, and quizzes. An exploratory implementation study on 15 DHH students who volunteered to use the module was conducted. The students’ interactions were monitored and the results of their pre and post-tests during the implementation of the module was analysed to determine if the module was effective for learning. The findings indicate that students could use the module based on their learning styles and were active interacting on Padlet. The results of the pre and post-tests show a significant increase in scores, indicating the effectiveness of the module. Hence, the module has the potential to improve understanding in graphic design among DHH students. The findings have implications on the design of modules for DHH and special needs students. This is in line with TVET aspiration, which is to provide equal access to quality education for all. Further investigation should be done to determine whether the module could be used for other programs involving special needs students.